Protein p0071, an armadillo plaque protein of adherens junctions, is predominantly expressed in distal renal tubules - Walter, Britta; Krebs, Ulrike Beate; Berger, Irina; Hofmann, Ilse (Histochemistry and cell biology, 2010)
Protein p0071 is a member of the p120-subfamily of armadillo proteins and is well known as a junctional plaque component involved in cell-cell adhesion, especially in adherens junctions. By systematic immunohistochemical analysis of mouse and human kidney tissues, p0071 was prominently detected in distinct kidney tubules. Upon double-labeling immunolocalization experiments with segment-specific markers, p0071 was predominantly localized in distal straight and convoluted tubules and to a lesser extent in proximal tubules, in the ascending thin limb of loop of Henle and in the collecting ducts. In capillaries of the kidney, p0071 co-localized with VE-cadherin an endothelium-specific cadherin. Protein p0071 was also detected in both, renal cell carcinomas derived from distal tubules and in maturing nephrons of early mouse developmental stages. Immunoblotting of total extracts of cultured cells of renal origin showed that p0071 was detected in all human and murine cells analyzed. Upon immunolocalization, p0071 was observed in adherens junctions but also in distinct cytoplasmic structures at the cell periphery of cultured cells. Possible structural and functional roles of p0071 are suggested by its preferential occurrence in distinct tubule segments, and its potential use as a cytodiagnostic cell type marker in renal pathology is discussed.
Online veröffentlicht am 15. Oktober 2009
Gesehen am 04.10.2023